Reconcilled to chestnuts roasting on a open fire and Jack Frost nipping at her nose, Colleen still could not get used to folks dressed up like Eskimos. - Harrop, Graham (Globe and Mail, 2003)
Reconcilled to chestnuts roasting on a open fire and Jack Frost nipping at her nose, Colleen still could not get used to folks dressed up like Eskimos.